Analisis Konsep Fluida Dalam Keterkaitan Alquran Dan Sains - Kanaya, Bulkis; Suliyanah, Suliyanah (IPF: Inovasi Pendidikan Fisika, 2023)
In everyday life, it is often found that ships sailing in the ocean move because of the wind and rain. The event contained the concept of physics, especially the concept of fluid which can be studied based on the Qur'an and science. This study aims to analyze the relationship between physics (science), especially the idea of fluid with verses contained in the Qur'an. The method used in this research is qualitative, namely literature review. The analysis used is based on the interpretation of Al-Mishbah, the interpretation of Ibn Kathir, and the interpretation of Jalalain as well as several articles from relevant research. The relationship between the concept of fluid and the Qur'an is found in the fluid characteristics described in Q.S. Al-Baqarah verse 164, Q.S. Al-Luqman verse 31, and Q.S. Al-Furqan verse 53. The concept of laminar and turbulent flow is explained in Q.S. Yunus verse 22 which discusses the types of fluid flow that drive ships sailing in the ocean. The relationship between pressure and fluid flow rate is explained by Q.S. Al-Baqarah verse 74. In addition, there is also an explanation of the relationship between temperature, air pressure, and fluid flow by Q.S. Al-Fathir Paragraph 9 which is also stated in the concept of the Bernoulli and Gay Lussac equation. Based on studies conducted on several verses of the Qur'an, it can be concluded that there is a relationship between the Qur'an and physics (science), especially in fluids, namely regarding fluid characteristics, types of fluid flow, fluid flow rates, and the relationship between temperature and pressure. on fluid flow. Keywords: Qur'anic, science, fluid